The Influence of Store Atmosphere and Service Quality on Customer Satisfaction - Sanjaya, Muhammad Adi; Dipayanti, Kris (Indonesian Development of Economics and Administration Journal, 2025)
The purpose of this research is to determine the effect of store atmosphere and service quality on customer satisfaction at Domino’s Pizza Bintaro Kesehatan branch in South Jakarta. Methodology/approach – This type of research uses associative research with a quantitative approach. The population in this research amounts to 22,540 consumers and the sampling technique uses the Slovin formula, sample of 100 respondents with data collection technique using a questionnaire. Data analysis includes validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. Findings – The results of this study indicate that store atmosphere (X1) has a positive and significant effect on consumer satisfaction. Service quality (X2) has a positive and significant effect on consumer satisfaction (Y). Store atmosphere (X1) and service quality (X2) simultaneously have a positive and significant effect on consumer satisfaction